2013
DOI: 10.1371/journal.pone.0076812
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Structural Characterization of SplD Protease from Staphylococcus aureus

Abstract: Staphylococcus aureus is a dangerous human pathogen. A number of the proteins secreted by this bacterium are implicated in its virulence, but many of the components of its secretome are poorly characterized. Strains of S. aureus can produce up to six homologous extracellular serine proteases grouped in a single spl operon. Although the SplA, SplB, and SplC proteases have been thoroughly characterized, the properties of the other three enzymes have not yet been investigated. Here, we describe the biochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 63 publications
(75 reference statements)
0
31
0
Order By: Relevance
“…Specifically, MgrA, SarR and SaeR each bring about profound upregulation of the spl operon, to levels that rival and, in the case of SaeR, exceed that of SarA and CodY for protease control. This is of interest because the Spls are well known for their narrow substrate specificity [5860]. Indeed, these enzymes share strong homology and many enzymatic characteristics with the exfoliative toxins of S. aureus .…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, MgrA, SarR and SaeR each bring about profound upregulation of the spl operon, to levels that rival and, in the case of SaeR, exceed that of SarA and CodY for protease control. This is of interest because the Spls are well known for their narrow substrate specificity [5860]. Indeed, these enzymes share strong homology and many enzymatic characteristics with the exfoliative toxins of S. aureus .…”
Section: Resultsmentioning
confidence: 99%
“…ETA was expressed in E. coli and purified, as earlier described . SplA, SplB, SplC, and SplD were expressed in E. coli , as described previously . SplE and SplF were purified as detailed in the supporting information (see supporting document: Supplementary Methods).…”
Section: Methodsmentioning
confidence: 99%
“…24,25 SplA, SplB, SplC, and SplD were expressed in E. coli, as described previously. [26][27][28][29] SplE and SplF were purified as detailed in the supporting information (see supporting document: Supplementary Methods). The purity of all preparations was at least 95%, as assessed by sodium dodecyl sulfate polyacrylamide gel electrophoresis.…”
Section: Staphylococcus Aureus Extracellular Proteasesmentioning
confidence: 99%
“…These are W/Y-L-Y-S/T for SplA [235], W-E-L-Q for SplB [233], and R-Y/W-P/L-T/L/I/V-S for SplD [236]. We therefore cannot predict any specific hits that are directly cleaved.…”
Section: Discussionmentioning
confidence: 97%
“…The Spl proteases are an intriguing area of study because, despite evidence that they contribute to S. aureus-host interaction, their specific functions have not been identified. Structural and activity analyses of SplA, SplB, and SplD have revealed that these enzymes are likely highly specific, given that they have cleavage preferences in subsites beyond the P1 residue of cleavage [232,233,235,236]. Further, the Spls are not produced as zymogens, but in some cases, appear to require binding of a preferred substrate in order to take on an enzymatically active conformation [232], as has been demonstrated by activity characterization of SplB [233].…”
Section: Discussionmentioning
confidence: 99%